Exploring the Influence of Open Data on Sustainable Development in Rwanda Through Information Technology (Journal of Economic Additions, 2025)
This research explores the role of open data in promoting sustainable development in Rwanda through IT. Using qualitative interviews with government, NGOs, and IT developers, it evaluates open data initiatives, infrastructure, and links to SDGs. Findings show improvements in transparency and decision-making via tools like the National Spatial Data Infrastructure. However, challenges persist, including limited internet, data inconsistencies, and lack of technical skills. Case studies such as e-Rwanda and community projects illustrate socioeconomic gains and rural development potential. The study emphasizes policy reform, capacity building, and stronger collaboration to maximize open data’s contribution to Rwanda’s 2030 development agenda.Jel Classification Codes : O33, O38, Q01, Q55, H83, D80, L86
Keywords: : Open Data, Sustainable Development, Information Technology, Rwanda, Data Transparency, Digital Infrastructure, Policy Implementation, Economic Growth, Data Accessibility, Innovation